Influence of pulse frequency on the morphology, structure and optical properties of ZnO films prepared by pulsed electrodeposition. (12th June 2019) - Caballero-Briones, F; Barón-Miranda, J A; Guarneros-Aguilar, C; Calzadilla, O; Sanz, F
Abstract: Zinc oxide films were grown at 65 °C by pulsed electrodeposition onto ITO substrates using as electrolyte solution 0.1 M Zn(NO3 )2 without supporting electrolyte. The potential was pulsed between OCP and −1300 versus Pt. ZnO films were measured by x-ray diffraction, UV–vis transmittance and scanning electron microscopy. The pulse frequency was varied from 1 to 100 Hz, with amplitude of 1300 mV and symmetric pulses. It was observed that the frequency has a major effect on film structuring with a big impact on the crystal habit and film thickness. The films were crystalline with different crystallographic orientation depending on the growth conditions with a band gap around 2.8–3.4 eV indicating a strong influence of the frequency on the electronic defects. The film growth mechanism and the film properties are discussed in terms of the effect of pulse frequency on the competing stages of nucleation-dissolution and Zn deposition-oxidation stages.